The Plurality and Minority in Religiousity (A Study on the Civil Right of Sunda Wiwitan Followers In Cigugur Kuningan) - Rustandi, Nanang (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2019)
The different belief among individual is an undeniable reality in history or man. The study on plurality and minority showed the dynamics of change in all parts of the world including in Indonesia. One of the local beliefs in Indonesia is Sunda Wiwitan. This article is aimed to observe the religiosity life especially the follower of Sunda Wiwitan in getting their civil rights as the citizens of a state. The study showed that there was a tendency of unfairness to the local belief followers especially in getting their civil rights. Whereas the power and ability of religiosity oriented to the multicultural which accept the plurality. The plurality acceptance was not taken for granted. It needed reinforcement and experience to be able to do religious deconstruction. The state, in this context, as the regulator should recheck the civil rights demand into the policies. Thus, it could give the same right for all the citizen including the local belief followers.